Materials and machine techniques for automated repair of bituminous pavements - Awuah, Frank Kofi Asamoah (2025)
Research has been conducted to evaluate the feasibility of automating crack and pothole repairs in bituminous pavements within a laboratory setting. Traditional manual methods, while effective, are labour-intensive, time-consuming, and prone to variability, underscoring the urgent need for automation to enhance efficiency, precision, scalability, and safety. To address these limitations, machines requiring minimal human input were developed alongside asphalt mixtures tailored for automated applications. A comprehensive review identified 3D printing as an optimal, economical, and user-friendly technology for creating repair machines. Accordingly, a RepRap 3D printer was modified for repair tasks, with parameters such as filling speed and extrusion temperature systematically optimised to improve repair quality.